Antifungal activity of green-synthesized curcumin-coated silver nanoparticles alone and in combination with fluconazole and itraconazole against Candida and Aspergillus species - Seyed Mohammad Amini; Muhammad Ebraim Getso; Shirin Farahyar; Sadegh Khodavaysi; Maryam Roudbary; Vahid Pirhajati Mahabadi; Shahram Mahmoudi (Current Medical Mycology, 2023)
Background and Purpose: Regarding the wide-spectrum antimicrobial effects of curcumin and silver, this study aimed to evaluate the antifungal activity of green-synthesized curcumin-coated silver nanoparticles (Cur-Ag NPs) against a set of Candida and Aspergillus species.Materials and Methods: Cur-Ag NPs were synthesized by mixing 200 µL of curcumin solution (40 mM) and 15 mL of deionized water. The mixture was stirred for 3-5 min, followed by the addition of 2.5 mL of silver nitrate solution (2.5 mM). The resulting solution was incubated for 3 days. Antifungal susceptibility of 30 fungal isolates of Aspergillus and Candida to fluconazole and itraconazole, as well as the activity of Cur-Ag NPs against the isolates, were determined, both alone and in combination, using broth microdilution according to the Clinical and Laboratory Standards Institute guidelines.Results: Cur-Ag NPs demonstrated promising antifungal activity, particularly against Candida species. The geometric mean value of the minimum inhibitory concentration of Cur-Ag NPs was significantly lower than that of fluconazole for all the studied fungi. Similarly, it was lower than those of itraconazole in C. albicans and A. fumigatus. The minimum fungicidal concentrations of Cur-Ag NPs were markedly better than those of fluconazole but still inferior to those of itraconazole.Conclusion: Cur-Ag NPs demonstrated indisputable antifungal activity and great potential that can be harnessed to combat fungal infections, particularly those caused by azole-resistant strains of Aspergillus and Candida.